Tissue Factor Signals Airway Epithelial Basal Cell Survival via Coagulation and Protease-Activated Receptor Isoforms 1 and 2 - Ahmad, Shama (American Thoracic Society, 2013)
Tissue factor (TF) initiates the extrinsic coagulation cascade and is a high-affinity receptor for coagulation factor VII. TF also participates in protease-activated receptor (PAR)1 and PAR2 activation. Human epithelial basal cells were previously purified on the basis of TF expression. The purpose of this study was to determine if tracheobronchial epithelial basal cell–associated TF drives coagulation and/or activates PARs to promote basal cell functions. We used human tracheobronchial tissues to isolate human airway epithelial cells using specific cell surface markers by flow cytometry and studied TF expression by immunostaining. TF-dependent fibrin network formation was observed by confocal and scanning electron microscopy. TF knockdown was done using short hairpin RNA, and TF mRNA was measured using quantitative RT-PCR. We found that 97 ± 5% of first-passage human tracheobronchial epithelial cells were basal cells, and 100% of these basal cells expressed TF. Basal cell–associated TF was active, but TF activity was dependent on added extrinsic coagulation cascade factors. TF inhibition caused basal cell apoptosis and necrosis. This was due to two parallel but interdependent TF-regulated processes: failure to generate a basal cell–associated fibrin network and suboptimal PAR1 and PAR2 activity. The data indicate that membrane surface TF mediates airway epithelial basal cell attachment, which maintains cell survival and mitotic potential. The implications of these findings are discussed in the context of basal cell–associated TF activity in normal and injured tissues and of the potential for repair of airway epithelium in lung disease.